Konsep Diri dan Kecemasan Remaja Putus Sekolah - Farikha Istiqomah; Abdul Amin (Ilmu Psikologi Universitas Yudharta Pasuruan)
Sometimes children who drop out also have anxiety. There are factors that can affect the emergence of anxiety in the individual such as, self-consciousness in the form of self-recognition, namely self-concept. This study aims to determinane the relationship of self-concept with the anxiety of drop out teenagers. Population in this research is adolescents in village and people “periphery” wich become population in this research counted 75 respondents who quit school from junior high school level to senior high school. Sample used in this research is in this research the sampling is done by purposive sampling technique non-random. Data collection using anxiety scale with the coefficient of validity between 0,303 to 0,403 with reliability coefficient 0,70947. While on the scale of self-concept obtained coefficient validity between 0,302 to 0,416 with reliability coefficient 0,72767. The results showed that from the results of research R arthmatic = 0,13988, F reg = -13,90 and R tabel 5% = 0,227. So, Freg -13,90 < R arithmethic 0,13988 < R table 5% < 0,227. The hypothesis which states there is a relationship of self-concept with the anxiety of drop out teenagers, rejected.